'Elementally' in motion - Manuela Valentini; Paola Donatiello (Pensa MultiMedia, 2023)
The new social orientation tends to isolate, within technological networks, social actors who increasingly adapt to an unnatural and myopic sedentarism. The COVID-19 pandemic has accentuated the needs of everyone, especially of children, who have been excluded from the pro-social and environmental dynamic environment. The aim of this essay is to reflect on the opportunities opened by the crisis understood as "decisive phase", from the Greek krísis "choice, decision". It is time to take action and ride the wave og change in order to approach new integrated educational models that can focus on the potential of motor skills, especially outdoors, related to learning, cognitive, emotional and physical improvement. The body, acted and primary learning agent, is necessarily in motion, involuntarily and ineluctably in an incessant search and discovery of Self, a Self placed in relation to the world and to the Others.